Pregnancy-Associated Chest Pain: A Case of Spontaneous Coronary Artery Dissection - Vidhushei Yogeswaran; Satvik Ramakrishna; John S. MacGregor; Lucas Zier; Nora Goldschlager (Case Reports in Cardiology)
Spontaneous Coronary Artery Dissection (SCAD) is an important cause of myocardial infarction that typically affects women without traditional cardiovascular risk factors. It is the most common cause of myocardial infarction in pregnant and postpartum women. SCAD is often underdiagnosed due to the lack of clinician familiarity, and patients with pregnancy-associated SCAD often have more severe clinical presentations than those without. We present a case of SCAD in a multiparous woman who presented with acute chest pain in the postpartum period.